Evaluation of the cervical cytology screening programme in an inner city health district. Issue 6691 (8th July 1989) - Beardow, R.; Oerton, J.; Victor, C.
Abstract : District health authorities have been instructed to operate a cervical cytology call and recall screening programme using the age-sex registers held by family practitioner committees. A detailed evaluation of implementation in an inner London district showed that 477 out of 687 (69%) invitation letters sent to women by the family practitioner committee were either inaccurate or inappropriate: almost half of the recorded addresses were incorrect and a further fifth of the women were not eligible for a test. Overall, 90 women had a smear, which is only 13% of the total but 43% of those found to be eligible. The findings did not differ significantly with age. The findings have major implications not only for the effectiveness of call and recall for screening for cervical cancer but also for the future development of screening for breast cancer in such areas.